Effective Strategies for Educating 7-Year-Old Children in Christian Education - Leorince Leorince; Hinsa Imanuel Cristoteles; Yurike Noviana Ferdinan Tambotto (Journal of Education Method and Learning Strategy, 2026)
Effective strategies for educating 7-year-olds in a Christian context are a crucial focus, as at this age, children learn from what they see and experience, and they need direct experience to understand the values ​​of faith. Challenges such as the influence of technology, secular culture, diverse learning styles, and limited parental involvement require a well-planned and contextualized educational approach. This study aims to understand the important focus on children in viewing technological developments. This study uses a descriptive qualitative method with a literature review approach, which refers to sources related to child education and Christian religious education. The findings indicate that effective strategies include child-centered learning, storytelling and experiential methods, creative activities (such as songs, drama, and games), the development of spiritual habits (prayer, Bible reading, and family worship), and the consistent application of love and discipline, supported by collaboration between family and church. Through a holistic and sustainable approach, faith-based education can shape children's character through love, discipline, empathy, and responsibility, so that Christian values ​​are not only understood but also practiced in daily life. This study fully contributes to the world of religious education by providing the right direction in educating children.